Aeromonas hydrophila Survives the Treatment of Posttraumatic Cellulitis in the Shelter of an Obscured Fish-Bone Fragment - Areti Ganiatsa; Constantina Gartzonika; Georgios Gaitanis; Paraskevi Voulgari; Stamatina Levidiotou-Stefanou; Ioannis D. Bassukas (Hindawi Limited, 2020)
Fish bone and/or spine puncture injuries can result in infection of the upper extremities with aquatic bacterial pathogens. Additionally, in such injuries, the inoculation of foreign organic material is frequent and may further complicate the clinical presentation and course of the resulting infection. We describe the case of a 45-year-old female patient with a minimal fish rostrum puncture trauma acquired during preparation of fresh fish meal, which resulted in a galloping hand cellulitis. The alarming clinical presentation and the prompt response of the skin infection to clindamycin obscured the presence of inoculated fish rostrum remnants in the tissue that, three weeks later, gave rise to a foreign body granuloma, from which Aeromonas hydrophila was isolated. Final resolution was achieved with an additional two-week doxycycline treatment. In conclusion, the reported case highlights the potential of the accidentally implanted organic material, as are fish bones, not only to transfer uncommon pathogens but also to offer a sanctuary that favors microbial survival despite antibiotic therapy thus enabling latent or recurrent infections.